Peningkatan Pengetahuan Gizi Ibu Hamil dengan Kekurangan Energi Kronis melalui Edukasi dan Pemberian Makanan Tambahan - AR, Irmayanti; Diana, Sitti Aras (Yayasan Inspirasi El Burhani, 2025)
Introduction: Chronic Energy Deficiency (CED) in pregnant women is a nutritional problem that can seriously affect pregnancy and fetal growth, including the risk of low birth weight (LBW), prematurity, and stunting. In the working area of Limboro Community Health Center, there are still pregnant women with a mid-upper arm circumference (MUAC) <23.5 cm, which indicates CED. Objective: To improve the nutritional status of pregnant women at risk of CED through nutrition education and the provision of locally sourced supplementary food (PMT). Method: This activity was carried out through a preliminary study and counseling about the importance of nutritional status in pregnant women with CED, delivered using lectures, group discussions, presentations, and leaflets. In addition, supplementary food (PMT) was also provided. Result: The MUAC measurement results showed that 13 pregnant women (56%) did not experience CED, while 10 pregnant women (44%) were identified with CED. Nutrition education increased participants’ understanding of the importance of nutrition during pregnancy, and the supplementary food was well received. Conclusion: Community service activities conducted in the Limboro Community Health Center area demonstrate that nutrition education accompanied by supplementary food provision can improve the knowledge of pregnant women and support better nutritional status.